Prominent alumni of UiTM / Nur Anisya Morshidi ... [et al.] - Morshidi, Nur Anisya; Syed Akil, Sharifah Nur Amirah; Guyang, Martina Emelda; Umbat, Anjeli (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Professor Dr Abang Zainoren bin Abang Abdurahman was born on 1st November 1963. He was named as one of the prominent alumni of the Faculty of Management and Business (FPP), UiTM Sarawak UiTMCS) who succeeded in academic leadership at the university.